Our way of being: Infant and Early Childhood Mental Health workforce development in Tennessee. Issue 6 (16th September 2021) - Morelen, Diana; Friday, Keena; Otwell‐Dove, Rebecca; Paradis, Nichole; Webster, Angela; Moser, Michele; Peak, Allison
Abstract: The optimal relational experiences of infants and young children demand a cross‐sector workforce informed by Infant and Early Childhood Mental Health (IECMH) principles and practices. A recent review by the Alliance for the Advancement of Infant Mental Health, Inc identified seven themes that help define "What makes an IECMH association strong?": (1) Identity, (2) Cross‐Systems Collaborations, (3) Sound Organizational Structure, (4) Competency‐Informed Training, (5) Reflective Supervision Capacity, (6) Policy, and (7) Higher Education. The present paper documents the story of the Association of Infant Mental Health in Tennessee (AIMHiTN) and the role of the Endorsement for Culturally Sensitive, Relationship‐Focused Practice Promoting IECMH in that growth across those seven themes with the additional themes of (8) Funding and, (9) Diversity, Equity, Inclusion, and Belonging. First, foundational literature is reviewed to summarize IECMH‐informed workforce development. Next, AIMHiTN's story of workforce development is mapped onto the nine themes and challenges and lessons learned are summarized. The article aims to serve as a roadmap for other states, provinces, territories, or nations hoping to develop their own Association for Infant Mental Health (AIMH) as well as a guide for those with existing AIMHs for promoting continued growth and sustainability. Resumen: Las óptimas experiencias de relaciones de los infantes y niños pequeñitos requieren de un sector heterogéneo de la fuerza laboral que esté informado acerca de los principios y prácticas de la salud mental en los infantes y en la temprana niñez (IECMH). Una reciente revisión por parte de la Alianza para el Avance de la Salud Mental Infantil, Inc.® identificó siete temas que ayudan a definir "¿qué hace fuerte a una asociación de IECMH?:" 1. Identidad, 2. Colaboraciones entre sistemas heterogéneos, 3. Buena estructura organizacional, 4. Entrenamiento con base en la competencia, 5. Capacidad para la supervisión con reflexión, 6. Políticas, y 7. Educación postsecundaria. El presente estudio documenta la historia de la Asociación de Salud Mental en Tennessee (AIMHiTN) y el papel que la Aprobación a Promover la Salud Mental Infantil y en la Temprana Niñez® para la Práctica de Sensibilidad Cultural Enfocada en la Relación juega en ese crecimiento a través de esos siete temas más los temas adicionales de 8. Fondos económicos y, 9. Diversidad, equidad, inclusión y sentido de pertenencia. Primero, la literatura básica se revisa para resumir el desarrollo de la fuerza laboral informada sobre IECMH. Después, la historia de AIMHiTN en cuanto al desarrollo de la fuerza laboral se despliega en los nueve temas y se resumen los retos y lecciones aprendidas. El artículo se propone servir como una especie de mapa de caminos a seguir para otros estados, provincias, territorios, o naciones que desean desarrollar su propia asociación de salud mental infantil (AIMH) así como también ser una guía para aquellos en donde ya existe una AIMH con el fin de promover el continuo crecimiento y sostenimiento. Résumé: Les expériences relationnelles optimales des bébés et des jeunes enfants exigent des effectifs intersectoriels ayant connaissance des principes et des pratiques de la santé mentale du nourrisson et de la petite enfance (IECMH). Une revue récente de l'Alliance for the Advancement of Infant Mental Health, Inc® a identifié sept thèmes qui définissent « Les forces de l'Association IECMH » : 1. L'identité, 2. Les collaborations intersectorielles, 3. Sa structure organisationnelle saine, 4. Sa formation centrée sur la connaissance des compétences, 5. Sa capacité de supervision réfléchie, et 7. L'enseignement supérieur. Cet article documente l'histoire de l'Association de Santé Mentale du Nourrisson de l'état du Tennessee aux Etats‐Unis (AIMHiTN) et le rôle de l'Adoption d'une Pratique Culturellement Adaptée et Focalisée sur la Relation, promouvant la Santé Mentale du Nourrisson et de la Petite Enfance dans ce développement au travers de ces sept thèmes avec deux thèmes supplémentaires : 8. Le financement et, 9. La diversité, l'équité, l'inclusion et l'appartenance. Les recherches fondatrices sont d'abord passées en revue afin de résumer le développement des effectifs suivi par l'IECHM. Ensuite l'histoire du développement des effectifs de l'AIMHiTN est mappé sur les neuf thèmes, les défis et les leçons apprises étant résumés. Cet article a pour but de servir de feuille de route aux autres états, provinces, territoires ou nations espérant développer leur propre association de santé mentale du nourrisson (AIMH) ainsi que de servir de guide à ceux ou celles ayant déjà des AIMH pour la promotion d'une croissance soutenue et d'une durabilité. Zusammenfassung: Unser Weg des Seins: Personalentwicklung im Bereich der psychischen Gesundheit von Säuglingen und Kleinkindern in Tennessee Optimalen Beziehungserfahrungen von Säuglingen und Kleinkindern erfordern eine sektorübergreifende Belegschaft, die sich an den Prinzipien und Praktiken der psychischen Gesundheit von Säuglingen und Kleinkindern (infant and early childhood mental health; IECMH) orientiert. Eine kürzlich von der Alliance for the Advancement of Infant Mental Health, Inc® durchgeführte Untersuchung hat sieben Themen identifiziert, mit deren Hilfe die Frage "Was macht einen IECMH‐Verbund stark?" beantwortet werden kann: 1. Identität, 2. systemübergreifende Zusammenarbeit, 3. solide Organisationsstruktur, 4. kompetenzorientierte Ausbildung, 5. reflektierte Supervision, 6. Politik und 7. Höhere Bildung. Die vorliegende Arbeit dokumentiert die Geschichte der Association of Infant Mental Health in Tennessee (AIMHiTN) und wie das System Endorsement for Culturally Sensitive, Relationship‐Focused Practice Promoting Infant and Early Childhood Mental Health® bezüglich dieser sieben Themen gewachsen ist. Zusätzlichen werden die Themen: 8. Finanzierung sowie 9. Vielfalt, Gleichberechtigung, Inklusion und Zugehörigkeit beleuchtet. Zunächst wird Grundlagenliteratur herangezogen, um die Thematik IECMH‐sensible Personalentwicklung zusammenzufassen. Anschließend wird die Geschichte der AIMHiTN‐Personalentwicklung anhand der neun Themen diskutiert und die Herausforderungen sowie Erfahrungen werden zusammengefasst. Der Artikel soll als Fahrplan für andere Staaten, Provinzen, Regionen oder Länder dienen, die einen eigenen Verbund für die psychische Gesundheit von Kindern aufbauen wollen, sowie als Leitfaden für diejenigen, die bereits über einen solchen Verbund verfügen, um kontinuierliches Wachstum und Nachhaltigkeit zu fördern. 抄録: 私達のあり方:テネシー州における乳幼児精神保健で働く人材開発 乳幼児が人との最適な関係を経験するには、乳幼児精神保健(IECMH)の原則と実践を熟知した多分野にわたる人材が求められる。Alliance for the Advancement of Infant Mental Health, Inc®が行った最近の調査によると、「何が乳幼児精神保健の団体を強固にするか？」を説明する7つのテーマを明らかにした。それらは、１.独自性、２.システム間の連携、３.健全な組織構造、４.能力に基づいたトレーニング(コンペテンシー・インフォームド・トレーニング)、５.内省的スーパービジョンを提供できる能力、６.方策、７.より高度な教育、である。この研究は、テネシー乳幼児精神保健協会(AIMHiTN)の経緯の話、及び文化的配慮があり関係性に焦点をあてた乳幼児精神保健を促進する実践に向けて、7つのテーマに 8.資金調達、と9.多様性、公平性、インクルージョン、そして所属感を加えて認定制度の役割を立証している。先ず最初に、乳幼児精神保健を熟知した人材開発を検証し要約する。そして次に、AIMHiTNの人材開発の経緯が9つのテーマそれぞれに描かれ、そして挑戦したことと学んだ事を説明する。論文を提出する目的は、乳幼児精神保健協会(AIMH)の発展を望む他の州、群、自治体、あるいは国の指針となり、現存のAIMHの促進が成長し持続可能であり続けるような指針となることである。 摘要: 婴幼儿的最佳关系体验需要一支以婴幼儿心理健康 (IECMH) 原则和实践为指导的跨部门劳动力。"婴儿心理健康促进联盟"最近的一项审查确定了有助于定义"什么使IECMH协会强大？"的七个主题:1.认同, 2.跨系统协作, 3.健全的组织结构, 4.胜任力培训, 5.反思性监督能力, 6.政策, 7.高等教育。本文记录了田纳西州婴儿心理健康协会 (AIMHiTN) 的事迹, 以及"认可文化敏感、注重关系的实践促进婴幼儿心理健康"在完善七个主题中的作用, 并涉及了其他主题:8.资金, 9.多样性、公平、包容和归属。首先, 回顾基础文献, 以总结以IECMH为指导的劳动力发展。接下来, AIMHiTN的劳动力发展事迹被映射到九个主题, 并总结了挑战和经验教训。本文旨在为希望发展自己的婴儿心理健康协会 (AIMH) 的其他州、省、地区或国家提供路线图, 并为已有AIMH的区域提供指南, 以促进其不断完善和可持续性。 ملخص: طريقتنا في الوجود: تطوير القوى العاملة في مجال الصحة النفسية للرضع والطفولة المبكرة في تينيسي تتطلب التجارب العلائقية المثلى للرضع والأطفال الصغار قوة عاملة عبر القطاعات مستنيرة بمبادئ وممارسات الصحة النفسية للرضع والطفولة المبكرة. وقد حدد استعراض منهجي أجراه مؤخراً التحالف من أجل النهوض بالصحة النفسية للرضع (IECMH) سبعة مواضيع يمكنها الإجابة على سؤال "ما الذي يجعل رابطة الصحة النفسية للرضع قوية؟" وهذه المواضيع تتلخص في : 1. الهوية ، 2. التعاون عبر النظم ، 3. الهيكل التنظيمي السليم ، 4. التدريب المستنير بالكفاءة ، 5. القدرة على الإشراف التأملي ، 6. السياسة ، و 7. التعليم العالي. توثق هذه الدراسة قصة اتحاد الصحة النفسية للرضع في تينيسي (AIMHiTN) ودور الدعم للممارسة الحساسة ثقافيا والمتمحورة حول العلاقة التي تعزز الصحة النفسية للرضع والطفولة المبكرة في هذا النمو عبر تلك المواضيع السبعة بالإضافة إلى مواضيع أخرى وهي : 8. التمويل و, 9. التنوع والعدالة والشمول والانتماء. في هذه الدراسة، تم مراجعة الدراسات السابقة لتلخيص موضوع تطوير القوى العاملة المستنيرة بمبادئ (IECMH). بعد ذلك ، تم مناقشة قصة اتحاد الصحة النفسية للرضع في تينيسي لتطوير القوى العاملة على المواضيع التسعة وتم تلخيص التحديات والدروس المستفادة. تهدف هذه المقالة إلى أن تكون بمثابة خارطة طريق للولايات أو المقاطعات أو الأقاليم أو الدول الأخرى التي تأمل في تطوير اتحادات خاصة بالصحة النفسية للرضع (AIMH) وكذلك كدليل للاتحادات الحالية لتعزيز النمو المستمر والاستدامة.